UJI EFEKTIVITAS DAYA HAMBAT EKSTRAK ETANOL DAUN KASTROLI (Euphorbia Heterophylla, L.) TERHADAP PERTUMBUHAN BAKTERI (Staphylococcus Aureus) - Muhammad Raihan Bagaskara; Irwandi Irwandi; Ratih Arum Astuti (Universitas Pendidikan Muhammadiyah Sorong, 2024)
Most infections are caused by bacteria. Bacteria that cause infections will continue to increase and will experience resistance, so it is necessary to optimize therapy, one of which is using plants that have antibacterial activity. The use of plants that have antibacterial properties is one treatment that can be used for infections caused by bacteria. One of the medicinal plants that needs to be developed is katroli (Euphorbia Heterophylla, L.). Traditionally, Indonesian people, especially in Eastern Indonesia, use castor oil as a cure for difficulty defecating. This study aims to determine the effectiveness of ethanol extract of castor leaves (Euphorbia Heterophylla, L.) with concentrations of 12.5 mg, 25 mg, 50 mg to inhibit the growth of bacteria (Staphylococcus Aureus). This research is a type of experimental research carried out using the disc diffusion method. The results of this research showed that there was a transparent zone on each paper disc with the concentration of ethanol extract of castor oil (Euphorbia Heterophylla, L.) known to be at a concentration of 50 mg. The diameter of the largest inhibition zone was 11 mm.